Urinary kynurenine,tryptophan, and neopterin concentrations during physiological pregnancy - Krčmová, Lenka Kujovská; Matoušová, Kateřina; Javorská, Lenka; Mrštná, Kristýna; Přívratská, Nikola; Suwanvecho, Chaweewan; Turoňová, Dorota; Farrag, Mohamed; Kacerovský, Marian; Melichar, Bohuslav (Scientific reports, 2025)
During pregnancy the alterations of kynurenine and tryptophan metabolism play an important role in local signalling and the prevention of fetal rejection. The aim was to investigate urinary levels of kynurenine and tryptophan during physiological pregnancy, and to determine their stability in urine during sample storage at different conditions. Urinary samples were obtained from 73 healthy pregnant women (median age 31 years), during the 1st, 2nd, and 3rd trimesters and from 42 healthy non-pregnant women (median age 30 years). Liquid chromatography methods using selective and sensitive mass spectrometry detection were used for analysis. Urinary neopterin, kynurenine, and tryptophan increased during the pregnancy and in comparison to the non-pregnant women. No correlation of the analytes with gestation age within each trimester and among the different analytes was observed. Kynurenine and tryptophan were stable in urine for 14 days at 4 °C, 6 months at - 22 °C, and 12 months at - 84 °C. Present results demonstrate differences in urinary concentrations of kynurenine, tryptophan, and neopterin between women with physiological pregnancy and healthy women. Simultaneous determination of kynurenine, tryptophan and neopterin may be explored in the disorders of pregnancy in future investigations.
Keywords: tryptofan; Chromatography, Liquid; Pregnancy; Humans; neopterin; Female; mladý dospělý; dospělí; kynurenin; Tryptophan; lidé; Adult; HPLC-MS/MS; Stability study; ženské pohlaví; chromatografie kapalinová; Urinary kynurenine; Urinary tryptophan; Healthy pregnancy; těhotenství; Neopterin; Young Adult; Kynurenine